Hydrothermally synthesized zinc oxide nanoparticles for reflectance study onto Si surface. (2020) - Dhasmana, Hrishikesh; Dutta, Viresh; Kumar, Amit; Kumar, Avshish; Verma, Abhishek; Jain, V.K.
Abstract: Herein, Zinc Oxide nanoparticles(NPs) are synthesized using hydrothermal method and are used to enhance Si-surface reflectance reduction for enhancing solar cell efficiency with simple and low cost method. The synthesis of ZnO nanorods are optimized by tuning parameters such as stirring time, ultrasonication time and vacuum drying. These NPs shape and size are characterized via XRD, TEM, UV–Visible and PL study. The structural analysis parameters such as preferred orientation, stress in NPs suggest that hydrothermally synthesized ZnO NPs has a problem of particle agglomeration which was resolved with suitable ultrasonication treatment and vacuum drying and the technique is able to produce well dispersed crystalline ZnO nanorods structures along with high aspect ratio. Thereafter, these NPs thin films are fabricated via spin coating onto textured Si surface and then reflectance measurement suggests absorption peak of ZnO in thin film at 370 nm. The reflection study of these NPs thin film are then compared with thin film of NPs synthesized via spray pyrolysis onto textured Si surface and show favourable reflectance reduction for NPs from spray pyrolysis from 15.1% to 11.44% in wavelength region 350–750 nm due to the porous structure. The study suggest that ZnO nanorod structure thin film onto textured Si is able to increase reflectance from existing 14% to 75% in the visible wavelength region 450–750 nm along with significantly decrease reflectance from 25% to 2.5% in wavelength region 350–370 nm.